RELEVANCE AND SIGNIFICANCE OF TECHNICAL COMMUNICATION COURSE CONTENTS: A CRITICAL EVALUATION IN THE STATE OF ANDHRA PRADESH - M.Nagaraja Kumar. S, Dr. Prasantha Kumar N. S (International Journal of Advanced Science and Technology, 2020)
In this world of gizmos, Master of Computer Application students are in dire need of enhancing their career opportunities and job prospects, possessing good communication and employability skills to achieve success in campus drives. To meet this demand, Technical Communication course in a three year MCA programme is viewed in a positive perspective in terms of reaching their goals and reducing the unemployment rate among Computer Application graduates.